The Value(s) of Vaccination: Building the Scientific Evidence According to a Value-Based Healthcare Approach - Calabro', Giovanna Elisa; Carini, Elettra; Tognetto, Alessia; Giacchetta, Irene; Bonanno, Ester; Mariani, Marco; Ricciardi, Walter; de Waure, Chiara (Frontiers in Public Health, 2022)
Objectives. To provide a new value-based immunization approach collating the available scientific evidence on the topic. Methods. Four value pillars (allocative, technical, personal and societal) applied to vaccination field were investigated. A systematic literature review was performed querying three database from December 24th, 2010 to May 27th, 2020. It included studies on vaccine-preventable diseases that mentioned the term value in any part and which were conducted in advanced economies. An in-depth analysis was performed on studies addressing value as key element. Results. Overall, 107 studies were considered. Approximately half of the studies addressed value as a key element but in most of cases (83.3%) only a single pillar was assessed. Furthermore, the majority of papers addressed the technical value by looking only at classical methods for economic assessment of vaccinations whereas very few dealt with societal and allocative pillars. Conclusions. Estimating the vaccinations value is very complex, even though their usefulness is certain. The assessment of the whole value of vaccines and vaccinations is still limited to some domains and should encompass the wider impact on economic growth and societies